GERAKAN LITERASI SEKOLAH TERHADAP MINAT BACA PESERTA DIDIK KELAS V SEKOLAH DASAR - Shanty Sulistyaningrum; Srie Mulyani; Neneng Sri Wulan (STKIP Subang, 2023)
In order to increase students' interest in reading, especially in elementary schools. It is undeniable that there are supporting factors and inhibiting factors during the implementation of the School Literacy Movement. The purpose of this research is to describe the implementation of the School Literacy Movement at SD Negeri 1 Nagrikidul. This type of research is qualitative with a case study design. The data collection techniques used are observation, interviews, questionnaires and documentation. The results of this study indicate that the implementation at SD Negeri 1 Nagrikidul has reached the learning stage. Supporting factors consist of the active role of all parties in the school, educators supervising literacy learning activities, a reading-friendly environment, all school parties producing written works, and support for the implementation of the School Literacy Movement at SD Negeri 1 Nagrikidul. The inhibiting factors are educators who do not make literacy learning effective, facilities and infrastructure are not comfortable, such as libraries that are not well organized and reading books in the literacy corner are also incomplete, and there is no special day for reading activities. The way to overcome this is that all schools hold a meeting regarding plans for the School Literacy Movement for the future, improve the administration of library management, add or update reading books so that it attracts students' attention to read. Based on the results of research data analysis, students' reading interest is currently in the high category. Therefore, the implementation of the School Literacy Movement in the future will remain consistent and have plans for the School Literacy Movement program so that it runs more conducive